Erlotinib and bevacizumab in patients with advanced non-small-cell lung cancer and activating EGFR mutations (BELIEF): an international, multicentre, single-arm, phase 2 trial. Issue 5 (May 2017) - Rosell, Rafael; Dafni, Urania; Felip, Enriqueta; Curioni-Fontecedro, Alessandra; Gautschi, Oliver; Peters, Solange; Massutí, Bartomeu; Palmero, Ramon; Aix, Santiago Ponce; Carcereny, Enric; Früh, Martin; Pless, Miklos; et al.
Summary: Background: The tyrosine kinase inhibitor erlotinib improves the outcomes of patients with advanced non-small-cell lung carcinoma (NSCLC) harbouring epidermal growth factor receptor ( EGFR ) mutations. The coexistence of the T790M resistance mutation with another EGFR mutation in treatment-naive patients has been associated with a shorter progression-free survival to EGFR inhibition than in the absence of the T790M mutation. To test this hypothesis clinically, we developed a proof-of-concept study, in which patients with EGFR -mutant NSCLC were treated with the combination of erlotinib and bevacizumab, stratified by the presence of the pretreatment T790M mutation. Methods: BELIEF was an international, multicentre, single-arm, phase 2 trial done at 29 centres in eight European countries. Eligible patients were aged 18 years or older and had treatment-naive, pathologically confirmed stage IIIB or stage IV lung adenocarcinoma with a confirmed, activating EGFR mutation (exon 19 deletion or L858R mutation). Patients received oral erlotinib 150 mg per day and intravenous bevacizumab 15 mg/kg every 21 days and were tested centrally for the pretreatment T790M resistance mutation with a peptide nucleic acid probe-based real-time PCR. The primary endpoint was progression-free survival. The primary efficacy analysis was done in the intention-to-treat population and was stratified into two parallel substudies according to the centrally confirmed pretreatment T790M mutation status of enrolled patients (T790M positive or negative). The safety analysis was done in all patients that have received at least one dose of trial treatment. This trial was registered withClinicalTrials.gov, numberNCT01562028 . Findings: Between June 11, 2012, and Oct 28, 2014, 109 patients were enrolled and included in the efficacy analysis. 37 patients were T790M mutation positive and 72 negative. The overall median progression-free survival was 13·2 months (95% CI 10·3–15·5), with a 12 month progression-free survival of 55% (95% CI 45–64). The primary endpoint was met only in substudy one (T790M-positive patients). In the T790M-positive group, median progression-free survival was 16·0 months (12·7 to not estimable), with a 12 month progression-free survival of 68% (50–81), whereas in the T790M-negative group, median progression-free survival was 10·5 months (9·4–14·2), with a 12 month progression-free survival of 48% (36–59). Of 106 patients included in the safety analysis, five had grade 4 adverse events (one acute coronary syndrome, one biliary tract infection, one other neoplasms, and two colonic perforations) and one died due to sepsis. Interpretation: The BELIEF trial provides further evidence of benefit for the combined use of erlotinib and bevacizumab in patients with NSCLC harbouring activating EGFR mutations. Funding: European Thoracic Oncology Platform, Roche.